The ANALISIS KINERJA SENSOR DHT22 DAN SENSOR LM35 PADA SUHU RUANGAN SERVER - Sulasmoro, Arfan Haqiqi; Yerry Febrian Sabanise; M. Teguh Prihandoyo (Universitas Muhammadiyah Surabaya, 2024)
A server room is a space for storing servers and network devices with certain security standards, including temperature regulation. Temperature is a crucial factor because of its influence on the performance of devices, especially electronic devices. Such influences include the performance of components, both semiconductors and capacitors, equipment life i.e. component wear, system reliability both physical and thermal and battery performance. So maintaining an optimal and stable temperature is very important to maintain the performance of electronic equipment. Performance analysis of DHT22 and LM35 sensors is needed to monitor the temperature and humidity of the server room, ensure optimal device performance, and reduce the risk of damage. The purpose of analyzing the performance of DHT22 and LM35 sensors is to compare the performance of the DHT22 sensor with LM35 for the temperature data obtained. The research method used is waterfall, which consists of the planning stage determining the block diagram for the design of the tool, the design of the microcontroller work flowchart to take the temperature with DHT22 and LM35, analyzing the data obtained, and implementation by installing the tool and taking data when running. The analysis results show that the DHT22 sensor is more accurate than the LM35 temperature sensor, where the DHT22 accuracy rate is 94.69% while the LM35 is 71.80%.